Associations between trajectories of social participation and functional ability among older adults: Results from the China Health and Retirement Longitudinal Study - Xu, Jiaqin; Xu, Jixiang; Chen, Yingwei; Wang, Yujie; Qin, Guoyou; Gao, Junling (Frontiers in Public Health, 2022)
Introduction Functional ability (FA) and social participation (SP) are important indicators of healthy aging, both their trajectories are heterogeneous. It is little known about how the SP trajectories affects FA trajectories. Methods FA was assessed by 20 items covering the ability of meeting basic needs and mobility. SP was assessed by frequency of participating in 10 social activities. Group-based trajectory modeling (GBTM) was used to identify the trajectories of FA and SP of the participants. Results Two FA trajectories were identified: low baseline-decline tendency (16.1%) and high baseline-stable tendency (83.9%) trajectories. Two SP trajectories were also identified: low baseline-stable tendency (58.5%) and high baseline-increase tendency (41.5%) trajectories. After controlling for the potential covariates, participants among the high baseline-increase tendency SP trajectory group also had significantly higher odds ratios to be belonged in high baseline-stable tendency FA trajectory group (ORs = 2.64, 95%CI = 1.98–3.05). Conclusions High-increasing social participation had a protective effect to maintain high baseline-stable tendency functional ability among older adults. These findings suggest social participation appears to have great benefits on promoting healthy aging in China.